Gustation assessment using the NIH Toolbox - Coldwell, Susan E. (Lippincott Williams & Wilkins, 2013)
The NIH Toolbox for Assessment of Neurological and Behavioral Function (NIH Toolbox) is a set of brief measures for the assessment of cognitive function, emotional health, motor function, and sensory function for use in clinical trials and in epidemiologic and longitudinal studies. Gustatory perception is assessed as 1 of 6 areas of sensory function. A team of 11 scientists with expertise in taste perception selected 2 gustatory measures, 1 of which can be used in young pediatric populations. The measure selected for young pediatric populations assesses sucrose (sweet) taste preference and can also be used across the age span of 5 to 85 years. For adult populations, the selected measure is a regional test, which assesses variability in perceived intensity of quinine hydrochloride (bitter) when applied to the tongue tip as well as perceived with the whole mouth. The team also recommends the regional test for assessing other tastants, such as sodium chloride (salty). Validation studies have demonstrated that the measures modified for the NIH Toolbox correlate with more traditional assessments, and can identify known population differences in gustation.